2012
DOI: 10.1556/achrom.24.2012.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Validated RP-HPLC method for the simultaneous determination of amlodipine besylate, valsartan, and hydrochlorothiazide in bulk and in pharmaceutical formulation

Abstract: A reverse-phase high-performance liquid chromatographic (RP-HPLC) method was developed for the simultaneous estimation of amlodipine besylate (AMB), valsartan (VAL), and hydrochlorothiazide (HCT) in pharmaceutical formulation using RP-C 18 column. The mobile phase (acetonitrile:methanol:50 mM phosphate buffer adjusted to pH 3 with orthophosphoric acid) was pumped at a flow rate of 1.0 mL min −1 in the ratio of 20:50:30% v/v and the eluents were monitored at 239 nm. Linearity was obtained in the concentration r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The reported method for simultaneous determination of HCZ, AML, and ALS ternary mixture was based on an ion pairing RP‐LC–UV technique using acetonitrile/25 mM octane sulfonic acid sodium salt monohydrate in water (60:40, v/v) as the mobile phase , whereas the proposed method is more conventional for analysis of that mixture. Regarding the reported method for simultaneous determination of HCZ, AML, and VAL, it was based also on a RP‐LC technique using acetonitrile, methanol and 50 mM phosphate buffer adjusted to pH 3 with orthophosphoric acid as the mobile phase in the ratio of 20:50:30, v/v and the eluents were monitored at 239 nm . On the other hand, Erturk et al reported a RP‐LC method for simultaneous determination of HCZ and MXP in tablets which was performed using a mobile phase consisting of acetonitrile and phosphate buffer (pH 4) (50:50, v/v) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported method for simultaneous determination of HCZ, AML, and ALS ternary mixture was based on an ion pairing RP‐LC–UV technique using acetonitrile/25 mM octane sulfonic acid sodium salt monohydrate in water (60:40, v/v) as the mobile phase , whereas the proposed method is more conventional for analysis of that mixture. Regarding the reported method for simultaneous determination of HCZ, AML, and VAL, it was based also on a RP‐LC technique using acetonitrile, methanol and 50 mM phosphate buffer adjusted to pH 3 with orthophosphoric acid as the mobile phase in the ratio of 20:50:30, v/v and the eluents were monitored at 239 nm . On the other hand, Erturk et al reported a RP‐LC method for simultaneous determination of HCZ and MXP in tablets which was performed using a mobile phase consisting of acetonitrile and phosphate buffer (pH 4) (50:50, v/v) .…”
Section: Resultsmentioning
confidence: 99%
“…So, it is necessary to develop a validated analytical method for assay of the cited drugs in combination with HCZ in their pharmaceutical preparations. A literature review revealed some published methods for simultaneous determination of one or more of the studied drugs in combination with HCZ using different analytical techniques such as LC–UV: ATN , VAL , MXP , ALS , AML , CND , LC–MS/MS: ATN , VAL , CND , UV spectroscopy: ATN , VAL , MXP , ALS , AML , CND , and CE: ATN , VAL , ALS , CND . To the best of our knowledge there is no method to separate the seven cited drugs.…”
Section: Introductionmentioning
confidence: 99%
“…These methods do not involve procedural steps and do not take more operator time and exper- tise like HPLC and other methods. In terms of simplicity, rapidity, sensitivity, expense and free from interference by common additives and excipients, the methods could be considered superior in comparison with the previously reported methods, especially with those based on chromatography [3][4][5][6][7] or other reported spectrophotometric methods [9][10][11]. The reagents utilized in the proposed methods are cheaper, readily available and the procedures do not involve any critical reaction conditions or tedious sample preparation.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive literature survey revealed that the determination of TDF in pure and dosage forms are not official in any pharmacopoeia and therefore, require much more investigation. Several analytical methods that have been reported for the estimation of TDF in biological fluids or pharmaceutical dosage forms include liquid chromatography [3][4][5][6][7], densitometry [8] and spectrophotometry [9][10][11].…”
mentioning
confidence: 99%
“…HPTLC and HPLC methods were also elaborated and validated in the range of official requirements [4,5,[7][8][9][10]. Similar chromatographic methods exist for amlodipine and valsartan in triple drug combinations [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%